Town Planning and Domestic Architecture in Ancient Mesopotamia from Earliest Times until the Middle of the Second Millennium B.C. - McAdam, Ellen (1981)
Thesis submitted to the Faculty of Oriental Studies for the Degree of Doctor of Philosophy. Volume 1: Text, volume 2: Illustrations; Supervisor: Roger Moorey; Available from The British Library, Document Supply Centre. Order No. D50069’84.